BS EN ISO 1833-22. Textiles. Quantitative chemical analysis. Part 22. Mixtures of viscose or certain types of cupro or modal or lyocell with flax fibres (method using formic acid and zinc chloride) (23rd June 2020) - British Standards Institution,
No abstract available